The Use of Deixis in Julia Gillard’s Speech on Commemoration of Bali Bombing Victims in Garuda Wisnu Kencana Cultural Park, Bali - Marta Dewi, Dewa Ayu (Humanis, 2018)
This paper is entitled The Use of Deixis in Julia Gillard’s Speech on Commemoration of Bali Bombing Victims in Garuda Wisnu Kencana Cultural Park, Bali. This research is aimed at analyzing the deixis used in the speech text by the Australia’s Prime Minister, Julia Gillard using Levinson’s theory. In conducting research, this study used qualitative method in which the study describes the types of deixis in which the data were taken from the Australian Minister website. Then identifying and classifying the deixis used in the speech text. The last step was  analyzing the data supported by the concept of Levinson. From all the data analysis taken from the speech text delivered by Julia Gillard, this study found the types of deixis such as person deixis, time deixis, place deixis, discourse deixis, and social deixis. This study also found some deixis in one sentence which help the speaker and the audience  understand the utterance better. This study suggests  the students in the future to use the other part such as analyzing an interview, conference, novels, and the like. Finally, such a big hope for this study could be useful to sharpen the reader in understanding deixis.